Epidermal keratinocyte-specific STAT3 deficiency aggravated atopic dermatitis-like skin inflammation in mice through TSLP upregulation - Wang, Zhao-Yuan; Zheng, Yu-Xin; Xu, Fan; Cui, Ying-Zhe; Chen, Xue-Yan; Chen, Si-Qi; Yan, Bing-Xi; Zhou, Yuan; Zheng, Min; Man, Xiao-Yong (Frontiers in Immunology, 2023)
Atopic dermatitis (AD) is one of the most common inflammatory skin diseases with complex pathogenesis involving epidermal barrier dysfunction, skin microbiome abnormalities and type-2-skewed immune dysregulation. Signal transducer and activator of transcription 3 (STAT3) is a transcription factor that plays critical roles in various biological processes. However, the role of STAT3 in epidermal keratinocytes in AD remains unclear. In this study, we generated an epidermal keratinocyte-specific Stat3-deficient mouse strain (termed Stat3 cKO mice). After topical 2,4dinitrochlorobenzene (DNCB) treatment, Stat3 cKO mice developed worsened AD-like skin inflammation with increased Ki67 + cells, decreased filaggrin and loricrin expression, and downregulated S100A9 and LL37. The dominant microbial population in Stat3 cKO mice changed from Ralstonia to Staphylococcus. DNCB-treated Stat3 cKO mice displayed more infiltrating type-2 inflammatory cells, including mast cells, eosinophils, and CD4 + T cells, accompanied by increased skin IL-4 and serum IgE levels. Moreover, thymic stromal lymphopoietin (TSLP), mainly produced by keratinocytes, was highly expressed in the ear skin of Stat3 cKO mice and chemoattracted more TSLPR + cells. TSLP blockade significantly alleviated DNCBinduced AD-like skin inflammation in Stat3 cKO mice. Thus, epidermal keratinocytespecific STAT3 deficiency can aggravate AD-like skin inflammation in mice, possibly through TSLP dysregulation.